Using resilience and passion to overcome bullying and lack of meaning at work: a pathway to change-oriented citizenship - De Clercq, D.; Pereira, R. (Journal of Organizational Effectiveness: People and Performance, 2023)
Purpose: This study adds to human resource management research by addressing relevant questions about how and when employees' suffering from workplace bullying may direct them away from voluntary efforts to improve the organizational status quo. It postulates a mediating role of beliefs about work meaningfulness deprivation, as well as beneficial, moderating roles of two personal resources (resilience and passion for work) in this link. Design/methodology/approach: The research hypotheses were tested with survey data collected among employees who work in the construction retail sector. Findings: A critical reason that bullying victims refuse to exhibit change-oriented voluntarism is that they develop beliefs that their organization deprives them of meaningful work, which, as the authors theorize, enables them to protect their self-esteem resources. The extent to which employees can bounce back from challenging situations or feel passionate about work subdues this detrimental effect. Practical implications: When employees feel upset about being bullied at work, their adverse work conditions may translate into work-related indifference (tarnished change-oriented citizenship), which then compromises employees' and the organization's ability to overcome the difficult situation. Managers should recognize how employees' personal resources can serve as protective shields against this risk. Originality/value: This study details the detrimental role of demeaning workplace treatment in relation to employees' change-oriented organizational citizenship, as explained by their convictions that their organization operates in ways that make their work unimportant. It is mitigated by energy-enhancing personal resources.